Advanced oxidation protein products in nondiabetic end stage renal disease patients on maintenance haemodialysis. (2nd December 2019) - Colombo, Graziano; Reggiani, Francesco; Astori, Emanuela; Altomare, Alessandra; Finazzi, Silvia; Garavaglia, Maria L.; Angelini, Claudio; Milzani, Aldo; Badalamenti, Salvatore; Dalle-Donne, Isabella
Abstract: In chronic kidney disease (CKD), the impairment of the excretory function leads to elevation in the blood concentrations of urea, creatinine, and various protein metabolic products. Advanced oxidation protein products (AOPP), along with protein carbonyls, protein-bound di-tyrosines and S -thiolated proteins, are considered biomarkers of oxidative stress in end-stage renal disease (ESRD) patients on maintenance haemodialysis (HD). In this study, we evaluated the correlations between plasma levels of AOPP (measured by size exclusion/gel filtration high performance liquid chromatography) and those of protein-bound di-tyrosines, protein carbonyls, albumin and fibrinogen in 50 nondiabetic ESRD patients on maintenance HD. Considering that AOPP could represent the bridge between oxidative stress and inflammation, having been identified as proinflammatory mediators, we also evaluated the association between AOPP levels, C-reactive protein concentration and white blood cells count. Finally, we assessed the associations between plasma level of AOPP and serum concentrations of creatinine and urea, both of which showed a strong dependence on the chronological age of haemodialysed patients. Taken together, our results confirm the robust relationship between uraemia and oxidative stress, especially when measured as biomarkers of severe protein oxidative damage (e.g. plasma AOPP).